Improving the creation of digital cards of nuclear power plants on the basis of MZM (Texas Journal of Engineering and Technology, 2024)
In this article, nuclear power plants are numerical improvement and geospatial mapping based on MZM emphasis is placed on placement issues. Nuclear power plants 1:10000 and 1 within a radius of 30 km of the planned construction area 1: 25000 from drones when updating scale cards The materials obtained were widely used in this data primary and the rest are auxiliary materials